2001
DOI: 10.1016/s0896-6273(01)00297-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of KCC2 Reveals an Essential Role of K-Cl Cotransport Already in Early Synaptic Inhibition

Abstract: KCC2 is a neuron-specific K +-Cl-cotransporter essential for establishing the Cl-gradient required for hyperpolarizing inhibition in the central nervous system (CNS). KCC2 is highly localized to excitatory synapses where it regulates spine morphogenesis and AMPA receptor confinement. Aberrant KCC2 function contributes to human neurological disorders including epilepsy and neuropathic pain. Using functional proteomics, we identified the KCC2-interactome in the mouse brain to determine KCC2-protein interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
461
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 528 publications
(487 citation statements)
references
References 42 publications
26
461
0
Order By: Relevance
“…Furthermore, several members of the cation-chloride co-transporter family are involved in hereditary diseases, such as Gitelman's, Bartter's, Gordon's and Andermann's syndromes, and have shown associations with bipolar disorder (Bianchetti et al, 1992;Dupre et al, 2003;Filteau et al, 1991;Gamba, 2005;Gitelman et al, 1966;Gordon, 1986;Howard et al, 2002bHoward et al, , 2003Meyer et al, 2005;Uyanik et al, 2006). The crucial role of cation co-transporters for neuronal development is also supported by animal studies in which knockout mice for cation-chloride co-transporters display a plethora of symptoms such as deafness, locomotor deficits, severe central and peripheral neurodegeneration, and sensorimotor gating defects (Boettger et al, 2002(Boettger et al, , 2003Hubner et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, several members of the cation-chloride co-transporter family are involved in hereditary diseases, such as Gitelman's, Bartter's, Gordon's and Andermann's syndromes, and have shown associations with bipolar disorder (Bianchetti et al, 1992;Dupre et al, 2003;Filteau et al, 1991;Gamba, 2005;Gitelman et al, 1966;Gordon, 1986;Howard et al, 2002bHoward et al, , 2003Meyer et al, 2005;Uyanik et al, 2006). The crucial role of cation co-transporters for neuronal development is also supported by animal studies in which knockout mice for cation-chloride co-transporters display a plethora of symptoms such as deafness, locomotor deficits, severe central and peripheral neurodegeneration, and sensorimotor gating defects (Boettger et al, 2002(Boettger et al, , 2003Hubner et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Cl Ϫ influx largely occurs via NKCC1, whereas Cl Ϫ efflux is mediated via the neuronalspecific K-Cl cotransporter KCC2 (11,(17)(18)(19). The importance of this regulation is underscored by the consequences of KCC2 deficiency in mouse, which reduces GABA's inhibitory signaling, resulting in motor defects, epilepsy, and anxiety-like behavior (20)(21)(22). The mechanism underlying the dynamic and coordi-nated modulation of NKCC1 and KCC2 activity in neurons is unknown.…”
mentioning
confidence: 99%
“…Disruption of NKCC1 in mouse leads to hearing loss, altered pain perception, neuronal excitability, and altered blood pressure (25). Targeted disruption of KCC2 results in epilepsy (20,21).…”
mentioning
confidence: 99%
“…As development proceeds, [Cl -] i is gradually decreased by the expression of the KCC2, and GABA becomes an inhibitory transmitter. Previous electrophysiological analysis directly demonstrated that KCC2-expression is crucial for the inhibitory transmission by GABA (Hubner et al, 2001;Okabe et al, 2003;Wang et al, 2005). Therefore, the molecular switch from NKCC1 to KCC2 drives the Cl -influx in response to ionotropic GABA receptor activation, and might be the beginning of the GABAergic inhibition.…”
mentioning
confidence: 99%